Islamic financial markets and institutions - Hassan, Abul, 1973-; Almaghaireh, Aktham Issa; Islam, Muhammad Shahidul (New York, NY : Routledge, 2023)
"The rapid pace of progress in the Islamic financial market and investment space, coupled with the COVID-19 pandemic and its aftermath and recovery, has provided the necessary challenges to build a strong case for Islamic investment. This timely and unique book focuses on the foundations of Islamic financial markets and institutions, in the context of various products, their market application, Islamic asset management and regulation. The authors provide a thorough overview of Islamic financing instruments and markets, such as Islamic debt and equity markets, through shares and the stock market, mutual funds, private equity, lease financing, sukuk, green sukuk, money market instruments, exchange traded funds, cryptocurrencies and derivatives etc., which have emerged as alternative sources of financing. They offer insight into the numerous infrastructure institutions which have sprung up since the first decade of the new century, such as The Accounting and Auditing Organizations for Islamic Financial Institutions, Islamic Financial Services Board, Islamic International Rating Agency and International Islamic Liquidity Management Corporation as well as those being established, to satisfy different industry needs. With its uniquely competitive approach to the mainstream financial market, this book facilities a greater understanding of the concept of Islamic investment. Through a discussion of the current state and future prospects of Islamic financial markets, the book's theoretical and practical approach offers academic, practitioners, researchers, students and general readers a well-balanced overview of Islamic financial markets, its ethics, Shari'ah foundation, the instruments and operational mechanism used by Islamic capital, money and debt markets"--
Keywords: Banks and banking -- Islamic countries; Banks and banking -- Religious aspects -- Islam; Finance -- Islamic countries; Financial services industry -- Islamic countries; BUSINESS & ECONOMICS / Finance